Genetic genealogy for cold case and active investigations. (June 2019) - Greytak, Ellen M.; Moore, CeCe; Armentrout, Steven L.
Highlights: Genetic genealogy is helping to close both cold and active investigations. Forensic DNA is uploaded to public genetic genealogy databases to find relatives. Extensive genealogy and descendancy research generate a list of possible identities. Many complicating factors can impede the research. Identity is narrowed down using a wide range of information & confirmed using STRs. Abstract: Investigative genetic genealogy has rapidly emerged as a highly effective tool for using DNA to determine the identity of unknown individuals (unidentified remains or perpetrators), generating identifications in dozens of law enforcement cases, both cold and active. The amount of press coverage of these cases may have given the impression that the analysis is straightforward and the outcome guaranteed once a sample is uploaded to a database. However, the database query results serve only as clues from which in-depth genealogy and descendancy research must proceed to determine the possible identities of an unknown individual. While there certainly will be more announcements of cases solved using this new technique, there are many more cases where identification has not yet been possible due to the wide variety of complications present in these investigations. This paper lays out the fundamentals of genetic genealogy, along with the challenges that are encountered in many of these investigations, and concludes with a set of case studies that demonstrate the variety of cases encountered thus far.